Implicit attitudes towards Genetically Modified (GM) foods: a comparison of context-free and context-dependent evaluations - Spence, Alexa; Townsend, Ellen (Elsevier, 2006)
Past research on attitudes towards GM food has focused on measuring explicit attitudes. Here we compared implicit attitudes towards GM foods with explicit attitudes towards GM foods. We used the Go No-Go task to investigate context-free implicit evaluations of GM foods and compared these with evaluations made in the context of ordinary and organic foods. Semantic differential scales were used to evaluate explicit attitudes towards GM foods. As expected, explicit attitudes towards GM foods were found to be neutral. However, contrary to our hypotheses, participants were found to hold positive, rather than neutral, implicit attitudes towards GM foods when these were assessed in a context free manner. In addition, neutral implicit attitudes were found when attitudes were assessed in the context of ordinary or organic foods, again contrasting with our hypotheses. These results imply that implicit attitudes towards GM food are more positive than anticipated and may lead to approach behaviour towards such products. Thus, given the choice, consumers are likely to accept GM food although other incentives may be needed if alternative foods are available.